Assessing village life and monument construction (cal. AD 65–1070) along the central Gulf Coast of Florida through stable isotope geochemistry. (December 2015) - Thompson, Victor D.; Pluckhahn, Thomas J.; Das, Oindrila; Andrus, C. Fred T.
Abstract: Given recent debates and reinterpretation of large-scale shell deposits as monuments rather than midden in the emerging dialogue in world archaeology regarding shell sites, we need better quantitative assessments of the temporality of shell deposit formation. Here we couple Bayesian analysis of radiocarbon dates with the results from our study of shell isotopes from C. virginica from the Crystal River and the Roberts Island Shell Mound Complex, neighboring and temporally overlapping shell mound sites on the central Gulf Coast of Florida. Linking these two lines of data is a new methodological approach which provides a more detailed understanding of the temporality of traditions. The results indicate that midden accumulation occurred throughout the year in the later phases of occupation at both sites. In contrast, oyster from mound deposits appears to indicate season of collection predominately during the colder months of the year. This contrast between mound and midden season of collection suggests that episodes of feasting and associated monument construction may have been of relatively limited temporal duration. Graphical abstract: Highlights: We link Bayesian modeling of radiocarbon dates with isotopic analysis of mollusks. Midden accumulation occurred year-round during later occupational phases. Mound construction occurred during the cooler months of the year. The data indicate shorter-term events related to feasting and monument construction.